Caregiver burden in lung transplantation: A review - Keerthana Sankar, MD; Anne Johnson, LCSW; Kathryn McRae, LCSW; Reinaldo Rampolla, MD; Nicholas A. Kolaitis, MD, MAS (JHLT Open)
Caregivers play a pivotal role in supporting patients undergoing lung transplant and often experience significant psychological, physical, and financial burdens. The current literature suggests that caregivers face heightened depression and anxiety in both the pre- and post-transplant periods. Caregivers of lung transplant patients may face unique challenges compared to other caregiver populations due to fears regarding pre- and post-transplant survival, lifestyle changes associated with post-transplant complications, and financial burden due to job loss and relocation. Caregiver well-being is linked to patient outcomes, with increased burden associated with higher post-transplant mortality. This review summarizes the symptoms associated with caregiver burden, assessment tools to evaluate caregiver strain, patient outcomes and social determinants of health as it relates to caregiver-patient relationships, and interventions to mitigate caregiver burden in the lung transplant population.